A Comparative Study of Macro- and Microstructures in al-Muʿjam al-Wasīṭ, Oxford Advanced Learner’s Dictionary, and Great Dictionary of the Indonesian Language: Implications for Digital Lexicography: Studi Perbandingan Makrostruktur dan Mikrostruktur dalam al-Muʿjam al-Wasīṭ, Oxford Advanced Learner’s Dictionary, dan Kamus Besar Bahasa Indonesia: Implikasi bagi Lexicografi Digital - Mafatihatul Maqhfiroh; Umi Kulsum; M. Husni T; Mawardi Yahya; Merry Choironi (Language Development Center, 2025)
Monolingual dictionaries play a crucial role in applied linguistics because they provide definitions and contextual meanings without involving another language. This study compares the macrostructure and microstructure of three monolingual dictionaries representing different linguistic traditions, al-Muʿjam al-Wasīṭ for Arabic, the Oxford Advanced Learner’s Dictionary (OALD) for English, and the Kamus Besar Bahasa Indonesia (KBBI) for Indonesian. Using a descriptive qualitative approach and content-analysis techniques, data were taken from dictionary entries and their presentation systems, supported by recent lexicographic literature in Arabic, English, and Indonesian. Results show fundamental differences in entry systems and lexical information. Al-Muʿjam al-Wasīṭ organizes entries by root (al-jadhr [الجذر]) and derivation (al-isytikāq [الاشتقاق]); the OALD highlights phonetic and collocational aspects, while the KBBI emphasizes normative and standardizing functions. The research concludes that the balance between macrostructure and microstructure determines dictionary effectiveness. It recommends developing a digital Indonesian monolingual dictionary that combines the Arabic morphological search system with the English-style richness of microstructural features.